Clients’ Satisfaction with Quality of Service Delivery at a Government Hospital in Ghana - Quartey, Perez; Ntekuni, Emmanuel (Advances in Social Sciences Research Journal, 2020)
Client satisfaction with health service delivery has been frequently used as an indirect measure of quality of service. Many healthcare delivery stakeholders and policy makers such as governments, health managers and clients alike are now attaching importance to healthcare quality. The main objective of the study was to examine the clients’ satisfaction with quality of healthcare at Atebubu Government Hospital. The mixed-method cross-sectional (both quantitative and qualitative) approach was adopted for the study. A structured questionnaire on five thematic areas (Infrastructure, Timeliness, Cost, Staff competence, Staff commitment and attitude) was used to interview exiting clients from the 7 units (Records, Consultancy, Pharmacy, Maternal and Child Health, X-ray, Laboratory and Ear, Nose and Throat). The study included a total of 1,470 clients. The overall mean perception level of the quality of service delivery and level of satisfaction were 69.8% and 70.8% respectively. The detailed breakdown of the responses showed that the mean scores for the Records (82.3%), Consultation (90.3%), X-ray (60.2%), Maternal and Child Health (80.1%), Ear, Nose and Throat (86.2%) were all satisfactory. However, the scores for the laboratory (48.3%) and pharmacy (48.1%) were both unsatisfactory mainly due to long waiting time and cost of accessing services. Clients’ satisfaction with quality of healthcare services at the Records, Consultancy, Maternal and Child Health, X-ray and the Ear, Nose and Throat departments were good. However, there was poor satisfaction with quality of services at the Laboratory and Pharmacy departments, with the main reasons for the dissatisfaction hinging on timeliness and cost.